Acute respiratory failure secondary to chronic obstructive pulmonary disease treated in the intensive care unit: a long term follow up study. Issue 1 (1st January 2002) - Breen, D; Churches, T; Hawker, F; Torzillo, P J
Abstract : Background: Traditionally, patients with acute respiratory failure due to chronic obstructive pulmonary disease (COPD) admitted to the intensive care unit (ICU) are believed to have a poor outcome. A study was undertaken to explore both hospital and long term outcome in this group and to identify clinical predictors. Methods: A retrospective review was carried out of consecutive admissions to a tertiary referral ICU over a 6 year period. This group was then followed prospectively for a minimum of 3 years following ICU admission. Results: A total of 74 patients were admitted to the ICU with acute respiratory failure due to COPD during the study period. Mean forced expiratory volume in 1 second (FEV1 ) was 0.74 (0.34) l. Eighty five per cent of the group underwent invasive mechanical ventilation for a median of 2 days (range 1–17). The median duration of stay in the ICU was 3 days (range 2–17). Survival to hospital discharge was 79.7%. Admission arterial carbon dioxide tension (Paco 2 ) and APACHE II score were independent predictors of hospital mortality on multiple regression analysis. Mortality at 6 months, 1, 2, and 3 years was 40.5%, 48.6%, 58.1%, and 63.5%, respectively. There were no independent predictors of mortality in the long term. Conclusions: Despite the need for invasive mechanical ventilation in most of the study group, good early survival was observed. Mortality in the long term was significant but acceptable, given the degree of chronic respiratory impairment of the group.